Pengaruh Fear of Missing Out (FOMO), Electronic Word of Mouth (EWOM), dan Price Terhadap Keputusan Pembelian Mie Gacoan di Samarinda - Muhammad Haikal Qardhawi; Zainal Abidin; Melda Aulia Ramadhani (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to determine and analyze the influence of Fear of Missing Out (FOMO), Electronic Word of Mouth (EWOM), and Price on the purchase decisions of Mie Gacoan in Samarinda. The rapid growth of the digital culinary industry has pushed social media to become a significant driver of consumer behavior. The population of this research includes residents of Samarinda who have purchased Mie Gacoan in the last three months and actively use social media. Sampling was conducted using a non-probability sampling method with a total of 150 respondents based on Hair's formulation guidelines. Data were analyzed quantitatively using Multiple Linear Regression analysis via IBM SPSS Statistics 22. The results of the partial analysis (t-test) showed that FOMO, EWOM, and Price each have a positive and statistically significant effect on consumer purchase decisions. Among all variables, Price was identified as the most dominant factor influencing purchase decisions, indicated by the highest regression coefficient. Simultaneously (F-test), FOMO, EWOM, and Price significantly influence purchase decisions altogether, accounting for 48.5% of the variance (R Square = 0.485). Culinary business actors should maintain affordable pricing models while consistently leveraging positive online reviews and viral social trends to maximize market growth.